(untitled) (Research, Society and Development, 2022)
Nature has always been a source of resources for human survival, but they also being saw in it an opportunity to use it for other purposes, starting to explore the pathogenic potential of many organisms in order to take economic and conflict advantages. Thus, measures were needed to control the access and use of these organisms, bioprotection. Such as many other issues, bioterrorism and bioprotection are difficult-to-approach topics. Thus, techniques are needed that make closer feasible and improve the approach to the topic with the students. The aim of this work was to carry out a literature review, a survey of activities and tools that can be used as means of approximation and scientific dissemination, within the theme of bioprotection and bioterrorism, proposing an extension course that arouses the interest of students.